Fraction B From Catfish Epidermal Secretions Kills Pancreatic Cancer Cells, Inhibits CD44 Expression and Stemness, and Alters Cancer Cell Metabolism - Jassim M. Al-Hassan; Daoyan Wei; Sharmistha Chakraborty; Tara Conway; Patrea Rhea; Bo Wei; Megan Tran; Mihai Gagea; Mohammad Afzal; Sosamma Oommen; Divya Nair; Bincy M. Paul; et al. (Frontiers Media S.A., 2021)
Pancreatic ductal adenocarcinoma (PDAC) is the fourth leading cause of cancer related death in western countries. The successful treatment of PDAC remains limited. We investigated the effect of Fraction B, which is a fraction purified from catfish (Arius bilineatus, Val.) skin secretions containing proteins and lipids, on PDAC biology both in-vivo and in-vitro. We report here that Fraction B potently suppressed the proliferation of both human and mouse pancreatic cancer cells in vitro and significantly reduced the growth of their relevant xenograft (Panc02) and orthotopic tumors (human Panc-1 cells) (p < 0.05). The Reverse Phase Protein Array (RPPA) data obtained from the tumor tissues derived from orthotopic tumor bearing mice treated with Fraction B showed that Fraction B altered the cancer stem cells related pathways and regulated glucose and glutamine metabolism. The down-regulation of the cancer stem cell marker CD44 expression was further confirmed in Panc-1 cells. CBC and blood chemistry analyses showed no systemic toxicity in Fraction B treated Panc-1 tumor bearing mice compared to that of control group. Our data support that Fraction B is a potential candidate for PDAC treatment.